2022
DOI: 10.20473/jaki.v10i1.2022.70-78
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Covid-19 Pandemic on Maternal Mortality Attributes

Abstract: Background: The COVID-19 pandemic is a challenge for mothers to access health services in Indonesia. Patient management, referral processes, and maternal screening protocols are the reasons for this issue. Aims: This study aimed to analyze maternal mortality trends in East Java Province before and during the COVID-19 pandemic. Methods: This study was conducted using retrospective observation with a cross-sectional design, and samples were selected using a total sampling technique. The number of maternal deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Based on data from the Directorate of Family Health, 1,086 mothers died as of September 14, 2021, due to COVID-19. 4 Factors that increase the risk of maternal death come from direct and indirect factors. Indirect factors such as age, health facility access, inadequate tools, and health services, access to knowledge, cultural practice, and poverty.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on data from the Directorate of Family Health, 1,086 mothers died as of September 14, 2021, due to COVID-19. 4 Factors that increase the risk of maternal death come from direct and indirect factors. Indirect factors such as age, health facility access, inadequate tools, and health services, access to knowledge, cultural practice, and poverty.…”
Section: Resultsmentioning
confidence: 99%
“…MMR is one indicator of the success of development in the health sector and describes the quality of maternal health. 4 However, efforts to achieve targets following the Sustainable Development Goals (SDGs) have been hampered due to COVID-19. Pregnant women are considered to be among the most vulnerable and at-risk populations in dealing with the spread of this virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brazil population-based cohort analysis of all pregnant women hospitalized with COVID-19, there were 1,858 maternal deaths (12.3%) out of 15,105 pregnancies, with a maternal mortality rate of 7.5 per 1000 patient-days [19]. In the province of East Java in Indonesia, the number of maternal deaths in 38 cities increased dramatically during the pandemic (2020) compared to before the pandemic (2019) (565 vs 520 deaths) [20]. One study from academic hospital in Surabaya (Indonesia) showed that maternal mortality directly caused by COVID-19 in pregnant women was signi cantly higher (OR: 6.91, 95% CI: 0.79-60.81) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal issues are classic issues in every edition of the Indonesian Journal of Health Administration. In this issue, our authors, Fatmaningrum et al (2022), revealed how the COVID-19 pandemic had increased the number of maternal deaths. Research conducted by Ernawaty and Sri (2022) again shows how big the risks Indonesian women must bear during pregnancy and childbirth are.…”
mentioning
confidence: 99%